Proceedings of the 25th International Symposium on Software Testing and Analysis 2016
DOI: 10.1145/2931037.2931057
|View full text |Cite
|
Sign up to set email alerts
|

Automatic test case generation: what if test code quality matters?

Abstract: Test case generation tools that optimize code coverage have been extensively investigated. Recently, researchers have suggested to add other non-coverage criteria, such as memory consumption or readability, to increase the practical usefulness of generated tests. In this paper, we observe that test code quality metrics, and test cohesion and coupling in particular, are valuable candidates as additional criteria. Indeed, tests with low cohesion and/or high coupling have been shown to have a negative impact on f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 41 publications
2
41
0
Order By: Relevance
“…Palomba et al [15] incorporated test cohesion and coupling metrics as secondary objectives within the preference criterion of MOSA to produce more maintainable test cases, from a developer point of view. Their approach produces more cohesive and less coupled test cases without reducing coverage.…”
Section: Background and Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…Palomba et al [15] incorporated test cohesion and coupling metrics as secondary objectives within the preference criterion of MOSA to produce more maintainable test cases, from a developer point of view. Their approach produces more cohesive and less coupled test cases without reducing coverage.…”
Section: Background and Related Workmentioning
confidence: 99%
“…While most of the research effort has been devoted to maximizing various code coverage criteria [2,6,8,9], recent work showed that further factors need to be considered for the generation of test cases [10][11][12][13]. Specifically, recent research investigated additional factors such as data input readability [11], test readability [13,14], test code quality [15], test diversity [16], execution time [12], and memory usage [10]. An early attempt to reduce the resource demand of generated tests is the work by Lakhotia et al [10].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations